2018
DOI: 10.1371/journal.ppat.1006959
|View full text |Cite
|
Sign up to set email alerts
|

Infection history of the blood-meal host dictates pathogenic potential of the Lyme disease spirochete within the feeding tick vector

Abstract: Lyme disease in humans is caused by several genospecies of the Borrelia burgdorferi sensu lato (s.l.) complex of spirochetal bacteria, including B. burgdorferi, B. afzelii and B. garinii. These bacteria exist in nature as obligate parasites in an enzootic cycle between small vertebrate hosts and Ixodid tick vectors, with humans representing incidental hosts. During the natural enzootic cycle, infected ticks in endemic areas feed not only upon naïve hosts, but also upon seropositive infected hosts. In the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 75 publications
0
35
0
Order By: Relevance
“…ospC is the most polymorphic gene in the genome of B. burgdorferi sensu lato (11)(12)(13) and encodes outer surface protein C (OspC). Studies have shown that OspC induces a strain-specific antibody response that protects rodents from tick bite (21)(22)(23)30). The two ospC alleles used in this study (the A3 and A10 alleles) have a genetic distance of 23.19% and an amino acid distance of 62.57%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ospC is the most polymorphic gene in the genome of B. burgdorferi sensu lato (11)(12)(13) and encodes outer surface protein C (OspC). Studies have shown that OspC induces a strain-specific antibody response that protects rodents from tick bite (21)(22)(23)30). The two ospC alleles used in this study (the A3 and A10 alleles) have a genetic distance of 23.19% and an amino acid distance of 62.57%.…”
Section: Discussionmentioning
confidence: 99%
“…There is no vertical transmission of B. burgdorferi sensu lato in either the tick (17) or the vertebrate host (18)(19)(20). In nature, vertebrate hosts develop a strong antibody response against B. burgdorferi sensu lato (18,19), and infection studies in rodents have shown that this antibody response is strain specific (21)(22)(23)(24). This antibody response is not effective at clearing the pathogen, which is why rodent hosts remain infected for months or even years (25)(26)(27)(28).…”
mentioning
confidence: 99%
“…Many strains of B. burgdorferi are maintained in the same local populations of infected mice and ticks, and host responses to 1 strain do not prevent infection with a different strain. It was recently found that the blood from a seropositive host profoundly attenuates the infectivity of homologous bacteria within the tick vector without killing them, thus preventing superinfection by homologous bacteria while facilitating transmission of heterologous B. burgdorferi strains [ 13 ]. In this section, we discuss how lipid immunogens, outer surface proteins, and live-mutant vaccines have been investigated for their potential to induce protective immune responses to B. burgdorferi infection and how any new Lyme disease host-targeted vaccines need to account for species and strain variability.…”
Section: Targeting the Spirochete In The Hostmentioning
confidence: 99%
“…Synthesis of OspC is induced during the blood meal while spirochetes reside in the tick midgut, and it is required by B. burgdorferi for host colonization [ 11 , 14 , 15 ]. Antibody-mediated immunity to OspC can prevent dissemination of homologous B. burgdorferi to the host [ 13 , 16 ] during early infection. However, due to OspC diversity, such protection is strain specific.…”
Section: Targeting the Spirochete In The Hostmentioning
confidence: 99%
“…Rather than strains actively facilitating each other in establishing infections, however, strain 372 aggregation in ticks may be a reflection of reservoir hosts being either free of spirochetes (in the 373 case of resistant and healthy hosts) or infected by multiple strains (in the case of susceptible and 374 weakened hosts). Regardless, it appears that once a host is infected by a strain, it becomes 375 susceptible for super-infection by additional, immunologically distinct strains (Bhatia et al, 2018). To summarize, we have established a next-generation sequencing-based, taxonomically 387 broad procedure that has the potential to become a standard protocol for detecting and quantifying…”
mentioning
confidence: 99%